Values underlying personnel/human resource management: Implications of the bishops' economic pastoral letter - Koys, Daniel J. (Journal of business ethics, 1988)
The economic pastoral letter states that employees have rights to employment, non-discriminatory treatment, adequate wages, health care, old age and disability insurance, healthy working conditions, rest and holidays, reasonable protection from arbitrary dismissal, notice of plant closings, unionization and collective bargaining. In addition, the bishops call for better cooperation between labor and management. This paper discusses how these rights can be protected by good personnel/human resource policies and procedures.